There Is no I in EAFM Adapting Integrated Ecosystem Assessment for Mid-Atlantic Fisheries Management. Issue 1 (2nd January 2021) - Muffley, Brandon; Gaichas, Sarah; DePiper, Geret; Seagraves, Richard; Lucey, Sean
Abstract: Resource managers worldwide are being asked to consider the ecosystem while making management decisions. Integrated Ecosystem Assessment (IEA) provides a flexible framework for addressing ecosystem considerations in decision making. The US Mid-Atlantic Fishery Management Council (Council) adapted the IEA approach and implemented a structured decision framework to address species, fleet, habitat, and climate interactions as part of their Ecosystem Approach to Fisheries Management (EAFM) in 2016. The Council's EAFM decision framework first uses risk assessment to prioritize fishery-ecosystem interactions for consideration. The Council's 2017 EAFM risk assessment identified a range of ecological, social, and management objectives or risk elements. Development of a conceptual model to identify key environmental, ecological, social, economic, and management linkages for a high-priority fishery is the second step in the framework. The Council identified summer flounder ( Paralichthys dentatus ) as a high-risk fishery and finalized an EAFM conceptual model that considers high-risk factors and ecosystem elements in 2019. The Council used the conceptual model to identify three priority summer flounder management questions (recreational data uncertainty, recreational discards, and distribution shifts) to be considered for quantitative management strategy evaluation, the third step in the EAFM framework and set to begin in 2020. Finally, as strategies are implemented, outcomes are monitored and the process is adjusted, and/or other priorities identified in the risk assessment can be addressed. The Council's rapid progress in implementing EAFM resulted from an extensive, positive, and collaborative process between managers, stakeholders, and scientists. Collaboration helps build trust and buy-in from all participants and is essential to IEA and to the success of EAFM.